(untitled) (Research, Society and Development, 2023)
Haff syndrome, or black urine disease, is triggered by the consumption of fish contaminated by a type of thermostable toxin, which is not destroyed even after its cooking. Not yet precisely identified, this toxin can trigger manifestations in the body that can range from mild symptoms to a picture of intense severity, when there is the development of rhabdomyolysis and renal impairment of the individual. Thus, early investigation and exclusion of differential diagnoses is of fundamental importance in order to start treatment as soon as possible. In this perspective, the objective of this review is to analyze the main clinical manifestations of the disease of black urine disease. This study is an integrative literature review, in which the platforms PubMed, SciELO, LILACS and Google Scholar were used as a search base for research of the scientific literature published between the years 2010 to 2023, in the Portuguese language.